ANALISIS WARNA BERBASIS SMARTPHONE ANDROID MENGGUNAKAN APLIKASI COLORIMETER PADA KALENDER POLIMEDIA TAHUN 2023 - Juwairiah, Juwairiah; Sinambela, Yusnia; Sitorus, Nurianti; Gobal, Raju; Sinaga, Romel (Kreator, 2024)
Abstract — The development of technology on Android has become a smart phone that can be accessed in the palm of your hand. Likewise in measuring the color of an image easily with the colorimetry application on an Android smartphone. In this colorimetric measurement using the Polimedia calendar case study for 2023. The working principle of the colorimeter is to measure the color of an object through three components, namely a light source, a light filter and a photoelectric detector. Each color has its own tristimulus value that distinguishes it from other colors. The colorimeter provides measurements that can be correlated with human eye-brain perception and provides real-time tristimulus (L, a, and b) values. The application of the colorimetry method to detect the dominant color of an image is quite fast in its detection. Consists of the colors Red, Green, and Blue (RGB). Broadly speaking, there are 3 colors used in the Polimedia calendar for 2023, namely scarlet violet (R: 57; G: 41; B: 103), silver (R: 189 G: 192 B: 199), (R: 185 G: 188 B:203), (R:190 G:197 B:215), (R:185 G:191 B:205), (R:190 G:198 B:211), (R:193 G:197 B : 209), Light Steel Blue (R: 190 G: 197 B: 215), (R: 190 G: 197 B: 215), (R: 185 G: 190 B: 209), (R: 192 G: 199 B: 217), (R: 187 G: 194 B: 212), (R: 190 G: 195 B: 214). Overall, the appearance of the 2023 Polimedia calendar is harmonious and balanced. There is overlap between design elements but does not provide significant interference. Typography has high legibility. Keywords: colorimetry, analysis, color, smartphone, android.